2022
DOI: 10.1038/s41366-022-01134-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of life-course patterns of adiposity with type 2 diabetes, depression, and their comorbidity in the Northern Finland Birth Cohort 1966

Abstract: Objectives Type 2 diabetes (T2D) and comorbid depression challenges clinical management particularly in individuals with overweight. We aim to explore the shared etiology, via lifecourse adiposity, between T2D and depression. Methods We used data from birth until 46years from Northern Finland Birth Cohort 1966 (n = 6,372; 53.8% females). We conducted multivariate analyses on three outcomes: T2D (4.2%), depression (19.2%) and as comorbidity (1.8%). We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Eleven 13,16,21,31,35,41,44–46,48,50,53 defined weight change between two time points, and the remaining six 23,25,27,29,37,39 defined trajectories of weight change based on three or more repeated measures of weight. Two 29,37 of these articles modelled population‐average trajectories using generalized estimating equations, and four 23,25,27,39 articles modelled heterogenous person‐centered trajectories using growth mixture modelling 25 or group‐based trajectory modelling 23,27,39 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven 13,16,21,31,35,41,44–46,48,50,53 defined weight change between two time points, and the remaining six 23,25,27,29,37,39 defined trajectories of weight change based on three or more repeated measures of weight. Two 29,37 of these articles modelled population‐average trajectories using generalized estimating equations, and four 23,25,27,39 articles modelled heterogenous person‐centered trajectories using growth mixture modelling 25 or group‐based trajectory modelling 23,27,39 …”
Section: Resultsmentioning
confidence: 99%
“…Conflicting results were reported in the two articles from the 1966 Northern Finland Birth cohort, which assessed weight change between different time points. Both studies were rated moderate quality, with one 48 using a combination of self‐report and measured BMI data and the other 21 defining depression using three heterogenous methods. The first study ( n = 8451) 48 showed females, but not males, with persistent overweight (including obesity) from age 14 to 31 years were at greater risk of depression at age 31 than the reference group comprising (1) women who were never overweight and (2) women with overweight confined to adolescence (OR: 1.4, 95% CI: 1.1, 1.9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk is posited to spiral from one generation to another, arising from adverse biological and environmental factors during gestation. Various in-utero adversities together have immediate consequences on birth outcomes and are also known to in uence the future burden of psycho-cardiometabolic disorders [5][6][7]. Along these lines our previous study identi ed four in-utero biopsychosocial latent factors that were, when combined, adversely associated with lower birth weight [8], which is a known risk factor for numerous diseases across the lifespan [9].…”
Section: Introductionmentioning
confidence: 99%